2013
DOI: 10.1158/1538-7445.am2013-5305
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5305: Transcriptionalregulation by microRNAs in NSCLC.

Abstract: Squamous cell lung cancer and adenocarcinoma are the most common subtypes of the lung tumours. The search for cancer-directed treatments has increased the need for understanding molecular features of either histological subtypes. The aim of this study was to identify the transcriptional regulation differences due to miRNA expression profiles between SCC and adenocarcinoma. In this work, a total of 44 patients were evaluated to assess the correlation between the miRNA and messenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Xie et al [101] found that over-expression of miR-21, miR-200b and miR-375, combined with a reduced level of miR-486, segregated patients with AD from those without, whereas down-regulation of miR-205, miR-210 and miR-708 could help to discriminate patients with SCC [111]. Of AD and SCC samples, six differentially expressed miRNAs (miR-149, miR-205, miR-375, miR-378, miR-422a and miR-708) and eight differentially expressed target genes (CEACAM6, CGN, CLDN3, ABCC3, MLPH, ACSL5, TMEM45B, MUC1) were validated [113]. In a recent study, paired miRNA and mRNA profiling was performed in 44 NSCLC tissue samples.…”
Section: Clinical Applications Of Mirnas In Nsclcmentioning
confidence: 99%
“…Xie et al [101] found that over-expression of miR-21, miR-200b and miR-375, combined with a reduced level of miR-486, segregated patients with AD from those without, whereas down-regulation of miR-205, miR-210 and miR-708 could help to discriminate patients with SCC [111]. Of AD and SCC samples, six differentially expressed miRNAs (miR-149, miR-205, miR-375, miR-378, miR-422a and miR-708) and eight differentially expressed target genes (CEACAM6, CGN, CLDN3, ABCC3, MLPH, ACSL5, TMEM45B, MUC1) were validated [113]. In a recent study, paired miRNA and mRNA profiling was performed in 44 NSCLC tissue samples.…”
Section: Clinical Applications Of Mirnas In Nsclcmentioning
confidence: 99%